The economic conditions in Al-Andalus during the periods of the Caliphate and the Emirate (Journal of the College of Education for Women, 2024)
The research addresses the economic aspect of Andalusia, which witnessed remarkable prosperity during both the Emirate and Caliphate periods. Andalusia enjoyed great diversity, noticeable stability, and development in various sectors. During the Emirate period (756-929), economic stability was achieved in all sectors. Agriculture received significant attention, along with advancements in irrigation systems and the variety of crops, which contributed to self-sufficiency. This led to the growth of trade and the export of surplus agricultural products. Trade played a major role in commercial exchange, aided by Andalusia's strategic location between the East and West. Foreign trade flourished, and the construction of markets in cities like Cordoba and Seville promoted local products, enhancing the importance of domestic trade. Handicrafts also developed, with paper manufacturing spreading widely, metalworking, textiles, glass, and pottery. This created numerous job opportunities and supported the local workforceto improve society's living standards, increase income, and alleviate poverty. During the Caliphate period (929-1031), economic development continued from the Emirate era, with improvements that further boosted the economy. New types of crops were introduced through trade with other countries, such as citrus and cotton, which were previously unavailable in Andalusia. Ports and coastal cities flourished, and silk production became an addition to the well-established industries, while handicrafts like weaponry manufacturing advanced. Intellectual culture thrived, libraries expanded, and books were translated, contributing significantly to the economy by fostering intellectual and scientific innovation to genera deas for further economic development.